1980
DOI: 10.48044/jauf.1980.075
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Bronze Birch Borer and Birch Dieback

Abstract: European white birch (Betula pendula) was the species most affected by birch dieback. Grey birch (B. populifolia) was occasionally affected. Paper birches (fi. papyrifera) showing symptoms of decline and dieback were rare. European white birches in good health rarely contained larvae of the bronze birch borer, Agrilus anxius. Trees in early stages of decline sustained borer larvae evenly distributed throughout the bole and main stem with lower numbers in the branches near the junction with the main stem. Trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Birch dieback is a serious problem of birch in the northern half of the United States. One study showed that over 40% of the European white birch (Betula pendula) in one midwestern city were exhibiting crown dieback (Ball and Simmons 1980). Birch dieback begins with the tree being altered by environmental stress (Batch and Prebble 1940).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Birch dieback is a serious problem of birch in the northern half of the United States. One study showed that over 40% of the European white birch (Betula pendula) in one midwestern city were exhibiting crown dieback (Ball and Simmons 1980). Birch dieback begins with the tree being altered by environmental stress (Batch and Prebble 1940).…”
mentioning
confidence: 99%
“…We believe that only certain trees have been sufficiently stressed to be vulnerable to attack. During the past several years, we have observed that birch dieback is a progressive process, and we have developed a crown vigor classification system to better illustrate this progression (Table 1) (Ball and Simmons 1980). A tree may alternate between class 1 and 2 for many years.…”
mentioning
confidence: 99%